Optimising multi-stakeholder practices in patient engagement: A gap analysis to enable focused evolution of patient engagement in the development and lifecycle management of medicines - Faulkner, SD; Pittens, CACM; Goedhart, NS; Davies, EH; Manning, E; Diaz-Ponce, A; Jose Vicente Edo, M; Prieto-Remón, L; Husain, L; Huberman, K; Boudes, M; Subramaniam, M (Springer, 2021)
Background The PARADIGM consortium aimed to make patient engagement in the development and lifecycle management of medicines easier and more effective for all, with the development of new tools that fulfil robustly defined gaps where engagement is suboptimal. Aims To generate an inventory of gaps in patient engagement practices and process from existing global examples. Methods A large set of criteria for effective patient engagement previously defined via a multi-stakeholder Delphi method, were mapped under fourteen overarching themes. A gap analysis was then performed by twenty-seven reviewers against the resulting forty-six mapped criteria, on a sample of seventy initiatives from global databases. Results An inventory of gaps was identified including contextual information as to why the gaps exist. Our work identified general patterns where patient engagement was suboptimal—defined as; fragmented reporting and dissemination of patient engagement activities, and the fundamental principles defined in frameworks or guidance being poorly adhered to in actual practice. Specific gaps were identified for sixteen criteria. Additionally, it was also common to observe primary aspects of a process were addressed for a given criteria (i.e. training for roles and responsibilities) but a secondary context element was lacking (i.e. making training material accessible/understandable/meaningful to all participants). Conclusion The results show that the evolution towards meaningful and systematic patient engagement is occurring, yet more importantly they provide clear directional insights to help enhance collaborative practices and co-design solutions. This targeted impact to catalyse a needs-oriented health system that integrates patient engagement at its core is essential.